1998
DOI: 10.1177/088307389801300204
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment of Children With Spina Bifida

Abstract: It was the aim of the present prospective study to investigate the influence of age, sex, intellectual function, and school type as well as of hydrocephalus, the level of lesion, and of the degree of handicap on the psychosocial adjustment of children with spina bifida. Seventy-five patients with spina bifida, aged 6 to 16 years were assessed concerning their psychosocial adjustment and their intellectual function by use of standardized instruments. The findings were compared with those of nondisabled controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…In the United States, anencephaly and spina bífida are the most commonly described CNS malformations, affecting 1:1000 gestations, and more than 300,000 patients worldwide 10 . Both spina bífida and anencephaly are significant causes of infant and fetal deaths 16 . Children with anencephaly usually die at birth or with a few hours of life.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, anencephaly and spina bífida are the most commonly described CNS malformations, affecting 1:1000 gestations, and more than 300,000 patients worldwide 10 . Both spina bífida and anencephaly are significant causes of infant and fetal deaths 16 . Children with anencephaly usually die at birth or with a few hours of life.…”
Section: Discussionmentioning
confidence: 99%
“…Yude and Goodman (1999) reported that children with physical disabilities were more likely to be rejected, isolated, and victimised by other children without disabilities, even when the physical disabilities were mild. Zurmohle et al (1998) also found children with physical disabilities (spina bifida) were at increased risk of poor social adjustment. Coster and Haltiwanger (2004) found that a substantial proportion of children with physical disabilities who were educated in general classrooms had below-expected levels of social skills.…”
Section: Introductionmentioning
confidence: 93%
“…Neurological severity indices of SB, such as level of lesion, shunted hydrocephalus, shunt infections, shunt revisions, and presence of epilepsy are important predictors of adaptation outcomes (Barf et al, 2003;Bergsten & Lagergren, 1990;Duquette, 1997;Fletcher et al, 2005;Iddon et al, 2004;Kim, 1991;Larsson, 1995;Matson et al, 2005;Pless, 1984;Shurtleff, 2000;Wallander & Thompson, 1995;Wallander & Varni, 1995;Wolman et al, 1994;Zurmohle et al, 1998). Level of lesion affects the quality and severity of motor and sensory impairment (Galli et al, 2002).…”
Section: Risk Factors For Poor Adaptationmentioning
confidence: 99%